2019
DOI: 10.1002/solr.201900235
|View full text |Cite
|
Sign up to set email alerts
|

From Macroscopic to Nanoscopic Current Hysteresis Suppressed by Fullerene in Perovskite Solar Cells

Abstract: In perovskite solar cells (PSCs), hybrid perovskite:fullerene phases are proposed to suppress macroscopic current hysteresis behavior by alleviating ion migration. However, the understanding of how fullerenes exactly alleviate the current hysteresis and what is the influence of fullerenes in such hybrid phases are still unclear from a microscopic viewpoint. Herein, the intentional incorporation of fullerene into perovskite is used to examine how fullerene exactly reduces the macroscopic current hysteresis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…This upward band bending helps spatial separation of photogenerated electron‐hole pairs and facilitates carrier collection at the GBs. In the following sections, the GB is demonstrated to be the main charge transport path by c‐AFM measurements, similar to our previous result [ 40 ] and other studies. [ 30–32 ] Under illumination, the photogenerated electrons transport along GBs and then immediately transfer into the contact layer TiO 2 .…”
Section: Resultssupporting
confidence: 90%
“…This upward band bending helps spatial separation of photogenerated electron‐hole pairs and facilitates carrier collection at the GBs. In the following sections, the GB is demonstrated to be the main charge transport path by c‐AFM measurements, similar to our previous result [ 40 ] and other studies. [ 30–32 ] Under illumination, the photogenerated electrons transport along GBs and then immediately transfer into the contact layer TiO 2 .…”
Section: Resultssupporting
confidence: 90%
“…This hysteresis mainly originates from the ionic motion within the perovskite. 49 In addition, the unbalanced charge transport in the PSC with a perovskite thickness of 250 nm results in the larger current hysteresis. 50 The smaller hysteresis in the PSCs with a perovskite thickness of 400 nm should be attributed to reduced interface-accumulated charges due to fast charge transfer from the perovskite to FTO.…”
Section: Resultsmentioning
confidence: 99%
“…All these devices show non-negligible current hysteresis. This hysteresis mainly originates from the ionic motion within the perovskite . In addition, the unbalanced charge transport in the PSC with a perovskite thickness of 250 nm results in the larger current hysteresis .…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that the PC 61 BM molecule undergoes an electron transfer reaction with the halogens from perovskite and binds them to the crystal GBs . When these I – ions are covalently attached to PC 61 BM molecules, their migration that drifted by an external field will be ineffective, so the current hysteresis is suppressed. When excess MA + ions are in the PC 61 BM, the PC 61 BM can only absorb part of the MA + ions, or most of the I – ions are free to move, and even into bulk perovskite, so there will be an obvious phenomenon of light soaking. The schematic illustration for the origin of light-soaking behavior is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%